1971
DOI: 10.1128/iai.3.4.559-561.1971
|View full text |Cite
|
Sign up to set email alerts
|

Latent Syphilis: Immunoglobulins Reactive in Immunofluorescence and Other Serological Tests

Abstract: Study of sera from 69 patients with untreated or inadequately treated latent syphilis revealed that immunoglobulin (Ig)G antibodies made up the bulk of the fluorescent treponemal antibody-absorption (FTA-ABS)-test reactivity found in the sera. IgM and IgA antibodies also contributed in some cases. Venereal Disease Research Laboratory slide-test reactivity was found in both 19 and 7S serum fractions, whereas Treponema pallidum immobilization-test reactivity was found mainly in the 7S fraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1981
1981
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…In the light of Hederstedt's work, our previous immunofluorescence studies of antibodies in early syphilis (9), and the current study, we can assume a uniform concept of action wherein the FTA-ABS and TPI tests gain their apparent specificity. Both assays incorporate factors which remove, suppress, or inactivate natural anti-T. pallidum reactivity in the sera of normal people, while allowing the recognition of immune antibodies in infected individuals.…”
Section: Downloaded Frommentioning
confidence: 62%
See 2 more Smart Citations
“…In the light of Hederstedt's work, our previous immunofluorescence studies of antibodies in early syphilis (9), and the current study, we can assume a uniform concept of action wherein the FTA-ABS and TPI tests gain their apparent specificity. Both assays incorporate factors which remove, suppress, or inactivate natural anti-T. pallidum reactivity in the sera of normal people, while allowing the recognition of immune antibodies in infected individuals.…”
Section: Downloaded Frommentioning
confidence: 62%
“…Gel filtration. Sera or Cohn fractions were fractionated by gel filtration through a bed of Sephadex G-200, 90 X 2.5 cm, as previously described (9).…”
Section: Materlkls and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conjugate was absorbed with Treponema phagedenis biotype Reiter with 1 part packed cells to 5 parts conjugate. The conjugate and cells were incubated at 37°C for 2 h, followed by holding at 2 to 8°C overnight (3). The bacterial cells were removed by centrifugation at 17,300 x g for 30 min, and the supernatant was filtered with a 0.45-ltm Millipore membrane filter.…”
Section: Methodsmentioning
confidence: 99%
“…In syphilis, as in many other infectious diseases, the early antibody response to infection is the production of IgM, rapidly followed by the appearance of IgG, which soon becomes predominant (18). In current studies, several workers have shown that the measurement of specific IgM antibodies to T.p.…”
Section: Discussionmentioning
confidence: 93%